Preparation and Characterization of Black Pomegranate Peel Extract-Loaded Nanofibers Using Electrospinning - Ali Heydari; Maryam Kouchak; Atefeh Raesi Vanani; Ali Kord Zanganeh (Journal of Kerman University of Medical Sciences, 2023)
Background: Blended electrospun nanofibrous mats containing black pomegranate peel extract (BPPE) were prepared using different proportions of polyvinylpyrrolidone (PVP) and polycaprolactone as the filament-forming polymers. Methods: The electrospinning process was conducted by simultaneously injecting PVP and polycaprolactone spinning solutions from two opposite sides on a rotary collector. The films were characterized in morphology, mechanical features, water vapor transmission rate, swelling properties, and drug release profile. Results: The uniform white porous nanofibrous mats were achieved using the optimized method. As the concentration of PVP in the formula increased, the average diameter of the fibers increased, and fibers containing spindle bodies appeared. Though, the moisture content is one of the most essential issues with a wound dressing to promote the healing process, excessive water absorption by PVP produced highly erodible mats with weak tensile strength and elongation. The higher content of polycaprolactone created narrower and more uniform fibers and improved the mechanical features and water swelling properties of the blended mats. Furthermore, the nanofibrous membrane composed of a 70:30 polycaprolactone/PVP weight ratio resulted in a more sustained drug release. Conclusion: The favorable properties mentioned above, along with the wound healing effect of BPPE, make it an attractive candidate for application in wound dressing products.